A case study on using district heating network flexibility for thermal load shifting. (October 2021) - Van Oevelen, Tijs; Scapino, Luca; Koussa, Jad Al; Vanhoudt, Dirk
Abstract: In district heating (DH) systems, the time of use of energy is becoming more important. For example, the use of sustainable baseload units over peak units is favored. Also heat production units coupled to the electricity grid, such as cogeneration plants and heat pumps, can profit from fluctuating prices and balance the electricity network at the same time. In this context, DH utility companies can benefit from shifting thermal loads in time. In the H2020 TEMPO project, a case study is being conducted to shift thermal loads using the thermal flexibility of the DH network. The thermal storage capacity of the network is utilized by dynamically changing the supply temperature. The study consists of two experimental campaigns, designed to dynamically characterize the available storage capacity in the DH network. In these campaigns, the supply temperature in one of the TEMPO demo sites was increased/decreased several times per day. The flow rate, supply and return temperatures were measured at the heat source and at a large customer building. The analysis of the experimental results focused on two aspects: the propagation of flow temperatures through the network and the response of customer substations to supply temperature changes. The data and knowledge gathered in these test campaigns will be used to develop models for a model predictive controller (MPC) which will be tested in the next heating season.